The selection of offering vessels in two Middle Mochica funerary contexts from Huaca el Pueblo - Úcupe, Zaña Valley, North Coast of Peru - Bryan Díaz, Bryan Daniel Joaquín (2024)
Archaeological research on Moche funerary contexts on the North Coast of Peru has focused on establishing the Moche social hierarchy, identifying rulers, priests or warriors according to the sumptuous objects displayed by the buried figures. However, the offerings of vessels, usually grouped around the deceased, which have been intentionally selected, have not been studied. This research aims to determine the social implications in the selection of offerings from vessels from Tombs 1 and 3 of Huaca el Pueblo-Úcupe. Two elite funerary contexts from the Middle Mochica phase, containing an adult man and an infant with 56 and 28 complete vessel offerings respectively. Through a morphological and decorative analysis, we conclude that the selection of vessels was made according to social canons of identity and religion.